2016
DOI: 10.11648/j.ajce.20160405.17
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Accident Patterns and Prevention Measures in Construction Sites in Nairobi County Kenya

Abstract: Abstract:Construction accidents don't just happen, they are initiated by unsafe acts, unsafe conditions or both. The construction industry in Kenya plays a vital role in achieving social and economic development goals, providing shelter, infrastructure, and employment. A study was carried out to identify the common accidents in construction sites and to examine the characteristics of the injured and deceased workers and evaluate factors that cause these accidents in Nairobi County, Kenya. The study cross exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 44 publications
4
8
0
Order By: Relevance
“…In this study, the odds of occupational injury were two times higher among workers who did not use PPE as compared to workers who use PPE. These results were consistent with the study done in Addis Ababa [7, 8], Nairobi, Kenya [20]. This consistency might be didn’t use PPE was no provision of PPE from the employers, negligence of workers and PPE were discomfort for the working condition of workers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the odds of occupational injury were two times higher among workers who did not use PPE as compared to workers who use PPE. These results were consistent with the study done in Addis Ababa [7, 8], Nairobi, Kenya [20]. This consistency might be didn’t use PPE was no provision of PPE from the employers, negligence of workers and PPE were discomfort for the working condition of workers.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the result showed that the odds of occupational injury who didn’t receive occupational health and safety training were 2 times more than workers who receive health and safety training. This result is in line with the study conducted in Gondar [9], Kenya [20], Ilam (Western Iran) [21]. This similarity might be workers participate in health and safety training increases their awareness and protect themselves from injuries.…”
Section: Discussionsupporting
confidence: 89%
“…This result is higher than the prevalence reports of studies done on construction workers in Gondar [13], 5 BioMed Research International Addis Ababa [12], South West Ethiopia [22], and Egypt [9]. It is lower than the results of the other two studies done in Addis Ababa, Ethiopia [14,15], and the other two studies conducted in Kenya [11,22]. However, it is closer to the prevalence reported from a study done in Malaysia [23].…”
Section: Discussionmentioning
confidence: 55%
“…Only 5 % to 10% of the workforce in developing countries has access to some kind of occupational health and safety services [6]. Literature showed that the prevalence of occupational injuries among construction workers at different countries was 30.1% in Iran [7], 30% in Turkey [8], 46.2% in Egypt [9], 71% in Illam (West Iran) [10], 74% in Kenya [11], and the prevalence varied between 38.3% [12], 38.7% [13], and 84.7% [14] in earlier studies done in Ethiopia. In a study conducted in Addis Ababa [14] sex, job satisfaction, workload, training, and personal protective equipment use were predictors of occupational injury.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown contradictory results regarding the repetition and diversity of work-related injuries among construction workers. For example, in some studies, slips and falls from height were the most prevalent work-related injuries (Hatami et al, 2017[ 15 ]; Jo et al, 2017[ 17 ]; Kemei and Nyerere, 2016[ 18 ]) while other studies including the present study, as well as the studies by Welch et al (2005[ 35 ]) and Cheng et al (2012[ 12 ]) have reported cuts and lacerations to be the most prevalent injuries. There are several reasons for the contradictory results of these studies.…”
Section: Discussionmentioning
confidence: 99%